RANCANG BANGUN ALAT PENGANGKAT TABUNG (GALLON) AIR MINUM COLLAPSIBLE - Handryan Habni; Eric Jobiliong; Anthony Riman (Cylinder : Jurnal Ilmiah Teknik Mesin, 2014)
‘Collaspsible’ is a concept of designing goods in terms of space saving. This concept could be applied in the draft of the design of Hansen (2008), “Lifter of gallon for potable water with mechanical system”, by way of decreasing the dimension of the tool’s folding function, sliding function and rolling function. Development of the design had led to a new tool with smaller dimensions than those of the previous one, namely length 31 cm, width 50 cm dan height 100 cm in comparison to previous dimensions which were length 50 cm, width 50 cm and height 139 cm. One unit lever which is connected to a gear box and double pulley was used for the manual mover. Implementing this kind of mover had caused a mechanical advantage of around 18 times, so that the force required to turn the lever amounts to 15 N. Common materials were used and they could easily be found in many utensil shops.